PENGARUH ECO-EFFICIENCY, GREEN INOVATION DAN CARBON EMISSION DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA LINGKUNGAN SEBAGAI MODERASI - Dading Damas; Rovila EL Maghviroh; Meidiyah Meidiyah (Jurnal Magister Akuntansi Trisakti, 2021)
The purpose of this study is to test, analyze and provide empirical evidence of theeffect of eco-efficiency, green innovation, disclosure of carbon emissions on firm value. The sample in this study were manufacturing companies that were listed and participated in the environmentalperformance rating assessment (PROPER) program as an environmental performance issued by the Ministry of Environment in 2014-2019 with a sampling method using purposive sampling criteria that collected 25 companies with 144 observations. The data analysis method used multiple linear regression. The results show that eco-efficiency has a significant negative effect, green innovation has a significant positive effect and carbon emission disclosure has a significant positive effect on firm value. Meanwhile, environmental performance can only strengthen the negative effect of eco-efficiency on firm value but cannot moderate the effect of green innovation and disclosure of carbon emissions on firm value.